Автоматизація процесу супроводження ургентних замовлень на компоненти крові в центрі служби крові - Кравченко, В. О. (ХНУРЕ, 2023)
This thesis explores the development of an algorithm called «Automation of the process of supporting urgent cases on blood components in the blood service center» which aims to automate the management of urgent orders and donor calls for blood donation. The algorithm simplifies order processing, reduces the workload of personnel, and speeds up the search for donors. During the work Use Case and Activity diagrams were created. A module «Tracking of urgent orders for blood components» will be created in the future for the information system of the blood center, based on the algorithm and diagrams developed.